61.3k views
1 vote
Simplify the expression

Simplify the expression-example-1
User Dundee MT
by
4.6k points

1 Answer

4 votes

Answer:

f(x) = 5x² + 2x

g(x) = 6x - 6

Explanation:


(5x^3-8x^2-4x)/(6x^2-18x+12)\\\\6(x^2-3x+2)\\e0\ \iff\ x=(3\pm√(9-8))/(2)\\e0\ \iff\ x\\e2\ \wedge\ x\\e1\\\\\\(5x^3-8x^2-4x)/(6x^2-18x+12)=(x(5x^2-8x-4))/(6(x^2-3x+2))=(x(5x^2-10x+2x-4))/(6(x^2-2x-x+2))=\\\\\\=(x[5x(x-2)+2(x-2)])/(6[x(x-2)-(x-2)]) =(x(x-2)(5x+2))/(6(x-2)(x-1))=(x(5x+2))/(6(x-1))=(5x^2+2x)/(6x-6)\\\\\\f(x)=5x^2+2x\\\\g(x)=6x-6

User Casey Falk
by
4.2k points